KEARIFAN LOKAL MASYARAKAT NELAYAN BAJO DALAM PEMANFAATAN SUMBERDAYA PERIKANAN DI DESA SEPATIN KECAMATAN ANGGANA KABUPATEN KUTAI KARTANEGARA - M. Sinar Alam; Eko Sugiharto; Fitriyana (2339-1324, 2015)
This study aims to identify and learn forms about characteristic of fishery resources in Sepatin Village, Anggana District, Kutai Kartanegara Regency. The method used in this thesis is a descriptive. The type of data used is primary type. Data collection techniques that writer use is the field research and the data analysis technique is quantitative analysis. The experiment was conducted for six months (January – July 2015). Sampling was done by a non-random based on consideration by 21 respondents. The results describe forms of Bajo Fishing Community in Sepatin Village, Anggana District are majority education level are elementary school, Islamic religion, age range 25-68 years, as well as the generally small-scale fisherman. The local livelihoods knowledge related of fishery resources use seen from they beliefs such as: Palace village tradition, food supplies (doko), pray for new boats (maddoa salama), ethical rules such as did not sail on friday, did not go to sea when the weather is bad or funeral ceremony was begun. Used fishing gear such as nets, lines, trawls, spear. To determine the extent of the fish are usually seen from sea water clarity and the birds flies above the water surface and conducted fishing activities at midnight and afternoon.